The South African Stock Market Reaction to Mergers and Acquisitions Transaction Attempts - Madume, Ndaedzo (Department of Finance and Tax, 2024)
This study investigates the reaction of the South African stock market to M&A transaction attempts. The aim is to understand, better, how unsuccessful M&A transactions are priced in a less-competitive market. By using a South African M&A dataset for companies listed on the JSE between 1997 and 2020, this study provides empirical evidence that, on average, in South Africa, acquiring firms earn positive abnormal returns for a few days before the transaction is announced for the first time in the market but negative abnormal returns after it is announced that the M&A transaction attempt has been unsuccessful. However, around the first announcement period, the target firms earn positive abnormal returns during a 5-day event window. The study also investigated whether the market punishes both the target and the acquiring firms for engaging in M&A transactions which could not be concluded found that the target firms earn negative abnormal returns at once but in contrast, the negative abnormal returns for the acquiring firm are delayed by five days. An event study methodology was used, and the sample size comprised of 44 JSE listed firms of which 31 were acquiring firms and 13 were target firms. This study is important because it provides insights into M&A using the most recent data. Furthermore, this research helps the parties involved to understand the market reactions to failed M&A transactions and gives insights into the determination of break-fees. Also, short-term investors can determine when their returns are more likely to be optimized if they should decide to trade in M&A events. This is important for M&A practitioners, asset managers, and for both the acquiring and target firms. It is also relevant to other market participants such as pension funds.